Association between ketamine use and mortality in critically ill patients receiving mechanical ventilation: Analysis of the MIMIC-IV database - Yuecheng Yang; Huanyu Luo; Yunkui Zhang; Zhiyong Zhao; Jun Zhang (PLoS ONE, 2025)
Objective Ketamine, as a sedative, has been administered during mechanical ventilation in critically ill patients; however, its impact on survival outcomes in this patient population remains uncertain. Methods This retrospective cohort study extracted data from the Medical Information Mart for Intensive Care (MIMIC-IV) database, version 3.0. Patients were categorized into the ketamine group and the control group based on whether ketamine was administered during mechanical ventilation. Propensity score matching was performed to adjust for demographic variables and coexisting conditions. The primary outcome was 28-day mortality. Secondary outcomes included 14-day and 90-day mortality rates, as well as hospital and ICU lengths of stay. Results The study included a total of 8569 patients, with 330 in the ketamine group and 8239 in the control group. After propensity score matching, significant differences in mechanical ventilation duration and the proportion of patients with acute respiratory distress syndrome remained between groups. No significant differences were observed in 28-day and 90-day mortality rates between the groups. Subgroup analysis indicated that ketamine was associated with lower 14-day mortality rates among younger patients, those with acute respiratory distress syndrome, and norepinephrine users. Ketamine administration was also found to correlate with increased lengths of stay in both the hospital and ICU. Conclusions Ketamine was more frequently selected for patients requiring prolonged mechanical ventilation. The administration of ketamine was associated with reduced 14-day but not with 28-day or 90-day mortality rates.